Usability of text input interfaces in smartphones. (1st January 2013) - Page, Tom
This paper reviews a number of different text input methods on smartphones and proposes how smartphone typing methods may inhibit user interaction rather than enhance it. It explores design and ergonomic considerations underpinning the use of six commonly used smartphone text input methods in order to determine and compare their usability. Furthermore, it discusses the results from testing smartphone users to assess which method is considered most efficient. It concludes that alternative input methods such as Swype and SwiftKey offer substantial benefits to users and are comparable with common typing speeds found on computer keyboards.